(untitled) (Journal of Biomedical Investigation, 2024)
BACKGROUND: The Return-to-work Assessment Scale (RAS) questionnaire is an outcome instrument used to measure the physical, psychological and social behavior and response of individuals to returning to work following injury or illness. This instrument has been validated in the English language, though here in Nigeria we have three (3) major languages: Igbo, Hausa and Yoruba. AIM: The aim of this study was to translate, culturally adapt and validate the Igbo version of RAS in order to enhance its use in Igbo speaking population. METHOD: This study was a cross-sectional survey involving 100 post stroke survivors. The original version of Return-to-work Assessment Scale (ERAS) was translated to Igbo (IRAS) and cross-validated. This Igbo version of RAS (IRAS) was subjected to reliability, validity and internal consistency. RESULT: The results revealed that 59 (59.0%) were males and 41 (41.0%) females. Internal consistency was high with a Cronbach’s alpha coefficient of 0.86 for Domain 1, 0.86 for Domain 2 and 0.87 for Domain 3. Test-retest reliability analysis gave an ICC of 0.99 (p=0.001) for Domain 1, Domain 2 an ICC of 0.99 (0.001), Domain 3 an ICC of 0.99 (0.001). The Kaiser-Meyer-Olkin measure of sampling adequacy (KMO) value for Domain 1 was X²=0.69 and that of Bartlett’s test of sphericity value was significant (p=0.001); Kaiser-Meyer-Olkin measure of sampling adequacy for Domain 2 was X²=0.80 and the Bartlett’s test of sphericity value was significant (P=0.001); the Kaiser-Meyer-Olkin measure of sampling adequacy for Domain 3 was X²=0.79 while the Bartlett’s test of sphericity was significant (p=0.001). CONCLUSION: The Igbo version of the Return-to-work Assessment Scale (IRAS) is a good, reliable and internally consistent tool for assessing readiness to return to work in Igbo stroke survivors.